Characteristics of Norovirus infection in Serbia - Relić Tijana; Begović-Lazarević Ivana; Pavlović Nevenka; Ilić Nevenka; Kačarević Hranislav; Jovanović Dara; Kostić Gordana; Lazarević Ivana (Vojnosanitetski Pregled)
Background/Aim. Norovirus (NoV), formerly Norwalk-like virus is the most common cause of acute gastroenteritis in humans of all ages. It is known that 90% of viral gastroenteritis and about 60-85% of all outbreaks of gastroenteritis, especially in the territory of United States of America, Europe and Japan are caused by this virus. For the countries of the northern hemisphere, individual cases and outbreaks of acute NoV gastroenteritis appear in seasonal pattern, mainly during the winter months. The aim of this study was to describe characteristics of acute gastroenteritis with the established NoV etiology in Serbia. Methods. The study group included 88 patients with the symptoms of acute gastroenteritis, throughout the year 2010 and 2011. From all the patients, stool samples were taken less than three days from the onset of symptoms. Detection of NoV in stool samples was performed by commercial qualitative immuno-chromatography assay. Statistical analysis included application of χ2 test, Mann-Whitney U-test, Kruskal-Wallis's test, Spearman’s rank correlation test and logistic regression analysis. Results. Outbreaks of acute gastroenteritis caused by NoV were recorded to be the most common in children with the incidence of infection of 50% in the age group 0-15 years. Analysis of individual symptoms in the NoV proven infection, showed that diarrhea was the most common symptom, followed by vomiting especially in small children, while abdominal pain was most common in elderly (≥ 65 years). The presence of frequent vomiting, more than 4 times/day, indicated NoV infection in the women, while for men the infection was always presented with diarrhea. Conclusion. The obtained results confirmed that small children and elderly are the most susceptible to NoV infection and that out-breaks are more frequent in the winter months. Those who consumed food in restaurants and other public facilities were not at higher risk for NoV infection.